PENGARUH PERTUMBUHAN EKONOMI, BELANJA MODAL, KESEJAHTERAAN MASYARAKAT TERHADAP KETIMPANGAN PENDAPATAN ANTAR DAERAH DI PROVINSI NUSA TENGGARA TIMUR - Novi Theresia Kiak (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT This study aims to determine how the influence of economic growth, capital expenditure and welfare affects the inequality of income distribution between districts / cities in East Nusa Tenggara Province. This research was conducted in the Regency / City of East Nusa Tenggara Province in 2014-2017. This research used panel data and was processed using eviews software. This research is expected to provide input to the East Nusa Tenggara provincial government. The results of this study indicate that among the three variables of economic growth, capital expenditure, and community welfare, economic growth only has a positive and significant effect. Based on these findings, the suggestion given is that district and city governments throughout the province of East Nusa Tenggara are deemed necessary to take strategic policies that are oriented towards increasing economic growth in the regions. by expanding employment opportunities, providing better economic infrastructure and in line with efforts to equal income distribution in the community, so that income inequality between regions can be minimized. Keywords : Economic Growth, Capital Expenditure, Welfare, Income Inequality between Regions